Electrochemical Immunochip Sensor for Aflatoxin M1 Detection - Parker, C.; Lanyon, Y.; Manning, M.; Arrigan, Damien; Tothill, I. (American Chemical Society, 2009)
An investigation into the fabrication, electrochemicalcharacterization, and development of a microelectrodearray (MEA) immunosensor for aflatoxin M1 is presentedin this paper. Gold MEAs (consisting of 35 microsquareelectrodes with 20 µm × 20 µm dimensionsand edge-to-edge spacing of 200 µm) together with onchipreference and counter electrodes were fabricatedusing standard photolithographic methods. The MEAswere then characterized by cyclic voltammetry, and thebehavior of the on-chip electrodes were evaluated. Themicroarray sensors were assessed for their applicabilityto the development of an immunosensor for theanalysis of aflatoxin M1 directly in milk samples.Following the sensor surface silanization, antibodieswere immobilized by cross-linking with 1,4-phenylenediisothiocyanate (PDITC). Surface characterization wasconducted by electrochemistry, fluorescence microscopy,scanning electron microscopy (SEM), and atomicforce microscopy (AFM). A competitive enzyme linkedimmunosorbent assay (ELISA) assay format was developedon the microarray electrode surface using the3,3,5',5'-tetramethylbenzidine dihyrochloride (TMB)/H2O2 electrochemical detection scheme with horseradishperoxidase (HRP) as the enzyme label. The performanceof the assay and the microarray sensor werecharacterized in pure buffer conditions before applyingto the milk samples. With the use of this approach,the detection limit for aflatoxin M1 in milk was estimatedto be 8 ng L-1, with a dynamic detectionrange of 10-100 ng L-1, which meets present legislativelimits of 50 ng L-1. The milk interference with thesensor surface was also found to be minimal. Thesedevices show high potential for development of a rangeof new applications which have previously only beendetected using elaborate instrumentation.